The Impact of Indonesian Law No. 6/2014 on Women’s Political Participation in the Politics of Kelurahan: A Study on Kelurahan’s Community Empowerment Institution (LPMK) in Salatiga, Indonesia - Ani Purwanti; Dyah Wijaningsih; Fajar Ahmad Setiawan (Faculty of Law, Universitas Jenderal Soedirman, 2019)
In Indonesia, decentralization and democratization have prompted the issue of women’s representation to be brought upon local and small-scale communities. One of the examples is the Indonesian Law No.6/2014 (the Village Act) in which the affirmative action for women’s participation is mandated in village’s representative body. Later, the same action is implemented in the urban counterpart to village’s rural that is Kelurahan, with the same Act –mutatis mutandis-. This article explores the implementation of Law No. 6/2014’s affirmative action to the kelurahan’s representative body, the Community Empowerment Institution or Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) in Salatiga. Acknowledging that there are fundamental differences between village and kelurahan, we found that such a maneuver has caused policy and practical inconsistencies where gender equality clause is omitted and the organization’s structure remains unreformed. Thus, it seems that the implementation of affirmative action for women participation in kelurahan’s politics has been withered before blooming.